2013
DOI: 10.1021/cm400517g
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding Luminescent Films of Nitrogen-Rich Carbon Nanodots toward Large-Scale Phosphor-Based White-Light-Emitting Devices

Abstract: In this work, nitrogen-rich carbon nanodots (CNDs) are prepared by the emulsion-templated carbonization of polyacrylamide. The formation mechanism and chemical structure are investigated by infrared, nuclear magnetic resonance, and X-ray photoelectron spectroscopies. Transmission electron microscopy also reveals that the obtained CNDs have well-developed graphitic structure and narrow size distribution without any size selection procedure. We vary the molecular weight of the polymer to control the size of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
88
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(94 citation statements)
references
References 40 publications
4
88
1
1
Order By: Relevance
“…For example, when the hollow carbon nanospheres are excited at wavelengths from 350 to 500 nm, the corresponding emission maxima shift from 430 to 540 nm. This excitation-dependent emission behavior is due to the presence of multiple surface emissive trap states, and then the radiative recombination of the excitons trapped in these states promotes the emission [16]. The strongest emission peak intensity locates at 510 nm when excited at 450 nm, which agrees with the excitation spectrum with a dominant peak at $450 nm.…”
supporting
confidence: 66%
“…For example, when the hollow carbon nanospheres are excited at wavelengths from 350 to 500 nm, the corresponding emission maxima shift from 430 to 540 nm. This excitation-dependent emission behavior is due to the presence of multiple surface emissive trap states, and then the radiative recombination of the excitons trapped in these states promotes the emission [16]. The strongest emission peak intensity locates at 510 nm when excited at 450 nm, which agrees with the excitation spectrum with a dominant peak at $450 nm.…”
supporting
confidence: 66%
“…[1,2] Studies have demonstrated that fluorescent CDs have ab road range of promising applications in bioimaging, [3][4][5] sensors, [6][7][8] photocatalyst [9,10] andw hite Light-Emitting Diodes (LEDs)e tc. [10][11][12][13][14][15][16][17][18][19] However,u pt on ow,a great number of studies have been focused on the synthesis and applicationso fa queous CDs, few attention wasp aid to solid powder CDs. This because CDs alwayss uffer severe luminescenceq uenching in solid powder form due to aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Doping provides an opportunity to tune the electronic energy levels for desired applications. Numerous synthetic strategies are available for preparingn itrogen-doped CDs from biological sources such as orange peels, [9] milk, [10] plant leaf, [11] cucumber [12] and so on, as well as from non-biological carbon precursors such as quinolone, [13] ammonium citrate, [14] polyacrylamide, [15] and so on. Ta ng et al showed that there is as ignificant change in the energy level structure of CDs doped with nitrogen and thus in their photoluminescence behavior.…”
Section: Introductionmentioning
confidence: 99%